Predicting Factors of fatigue in Postpartum mothers undergoing Cesarean section in Northern Thailand - Chaeye, Kanyapat; Phanvatr, Amornlert; Kabmala , Prapaisri (Journal of Nursing, Siam University, 2021)
The research was aimed at examining level and predictive factors for fatigue in postpartum mothers who have undergone cesarean section in northern Thailand. The data were collected from 259 postpartum mothers 48, and 72 hours after cesarean section at postpartum wards or gynecological wards of 9 hospitals in northern Thailand. The data were collected using a questionnaire. The questionnaire consisted of 6 parts, namely 1) demographic data, 2) medical records, 3) the postoperative pain wound, 4) postoperative fatigue, 5) sleep disturbances and 6) the maternal role stress. Data collection took place during the period of July 2018 to October 2019. Descriptive statistics and multiple regression were used to analyze the data. The results revealed that mothers had a moderate level of fatigue after 48 hours and also 72 hours after birth. The postoperative pain wound, sleep disturbance and maternal role stress were found to be the predictors and could explain 28.10% and 12.10% of the variances in fatigue at 48 hours and 72 hours after birth. Conclusion: Mothers should be planned to arrange the postoperative wound pain, promoting maternal sleep and adjust appropriately stress management in a postpartum maternal role. There can help the mother to reduce fatigue after the cesarean section.